Product Quality, Price, Promotion, and Loyalty: The Mediating Role of Satisfaction at RSU Adhyaksa Sehat Sejahtera Berdikari Cooperative - Sayogo, Muhammad Miftachul Huda Alvin; Nora, Liza; Hadi, Lukman (Community Engagement and Emergence Journal (CEEJ), 2025)
The purpose of this study is to examine how customer satisfaction at the RSU Adhyaksa Sehat Sejahtera Berdikari Cooperative influences the loyalty of Samsung entry-level series smartphones consumers in relation to product quality, price, and promotion. The methodology is quantitative and of the associative research type, and the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) is utilized to analyze the data.The study's findings show that customer satisfication is significantly impacted by pricing, marketing, and product quality. Additionally, customer loyalty is significantly impacted by these three factors. Customer loyalty has been shown to be significantly impacted by customer satisfaction. Additionally, the link between pricing, promotion, and product quality and customer loyalty is strongly mediated by consumer satisfaction.Thus, it can be concluded that customer satisfaction plays an important role in strengthening the relationship between product quality, price, and promotion on the loyalty of Samsung entry-level series smartphones users. This study provides practical implications for companies in improving marketing strategies through quality improvement, price adjustments, and effective promotions to increase customer loyalty.